2014
DOI: 10.1016/j.juro.2013.08.019
|View full text |Cite
|
Sign up to set email alerts
|

A New Concept for Early Recovery after Surgery for Patients Undergoing Radical Cystectomy for Bladder Cancer: Results of a Prospective Randomized Study

Abstract: Early recovery after surgery of patients who underwent radical cystectomy appears to have significant benefits compared to a conservative regimen in terms of postoperative morbidity, quality of life, use of analgesics and time spent in the intermediate care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
108
0
6

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(115 citation statements)
references
References 15 publications
1
108
0
6
Order By: Relevance
“…This suggests the details matter and that is not ethereal shifts in expectations the drive improvement. This is consistent with several prospective randomized controlled trials examining the impact of ERAS protocol implementation on patient outcomes [14, 3537]. In addition, several investigators have also reported on the improved outcomes having higher compliance with ERAS components [5, 37, 38].…”
Section: Discussionsupporting
confidence: 87%
“…This suggests the details matter and that is not ethereal shifts in expectations the drive improvement. This is consistent with several prospective randomized controlled trials examining the impact of ERAS protocol implementation on patient outcomes [14, 3537]. In addition, several investigators have also reported on the improved outcomes having higher compliance with ERAS components [5, 37, 38].…”
Section: Discussionsupporting
confidence: 87%
“…219,220 With respect to preoperative nutrition, up to 33% of urology patients undergoing surgery are at nutritional risk. 221 Preoperative malnutrition independently increases the mortality rate, 222 but its impact on morbidity has not been studied.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis across surgical specialities has shown the efficacy of fast-track programmes in reducing LOS and early complications within 30 days [5]. Reports from surgical societies on the implementation of fasttrack interventions in major urological surgery are lacking, although recent studies have challenged innovative pathways [7,8]. The exact nature of the successful fast-track intervention in RC may be difficult to define.…”
Section: Introductionmentioning
confidence: 99%